PENGARUH PENERAPAN STANDARD RECIPE TERHADAP KUALITAS PRODUK DI D’COLONEL BOGOR - Aggy Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2021)
Research to examine the analysis of the implementation of the standard recipe application, the authors conclude that the food produced has passed the standard and the kitchen employees carry out the standard recipe application well. The purpose of this study was to determine the application of standard recipe factors in restaurants. The design of this research is observation to the object of research, interviews with kitchen employees, distributing questionnaires to restaurant customers, and literature studies to support the theories used by the author in this study. Data analysis used in this research is descriptive analysis method with case studies. The conclusion of this study is, From the results of distributing questionnaires distributed to several employees, the results are that the head chef is right to convey the material well, this is evidenced by the results of research which states the number 35, which means agreeing to the statement.